On the Emergence of Cooperative Industrial and Labor Relations - Gabriele Cardullo; Maurizio Conti; Andrea Ricci; Sergio Scicchitano; Giovanni Sulis (Global Labor Organization (GLO), 2023)
We explore the long run determinants of current differences in the degree of cooperative labor relations at local level. We do this by estimating the causal effect of the medieval communes -that were established in certain cities in Centre-Northern Italy towards the end of the 11th century- and that contributed to the emergence of a cooperative attitude in the population on various proxies for current cooperative labor relations. Conditional on a large set of firm and municipality level controls, as well as a full set of province fixed effects, we find that firms located in municipalities that had been a free medieval commune in the past, have higher current probabilities to adopt two-tier bargaining structures and to be unionized. We also report IV and propensity score estimates that confirm our main results.
Keywords: J50; J53; J59; N00; 330; Industrial relations; Two-Tier Bargaining; Unions; Cooperation; Persistence